Pengaruh Kepercayaan Konsumen Terhadap Keputusan Pembelian Online Pada Marketplace Tiktok Shop di Kalangan Mahasiswa Universitas Muhammadiyah Riau - Rahmayanti, Sri; Hadi, M. Fikry; Radianti, Nabilla (Akuntansi & Ekonomika, 2023)
This study uses quantitative methods to determine whether consumer confidence on their decision to make online purchases in the Tiktok Shop market among students of Universitas Muhammadiyah Riau. This study used a sample of 100 students who are Tiktok shop customers. This study found that the Consumer Trust variable (X) has a tcount value greater than the ttable, namely 14.569 greater than 1.984, and a significant level of 0.000 greater than 0.05. The hypothesis results show that H0 is rejected and H1 is accepted, which indicates that there is a positive and significant influence between increasing Consumer Trust (X) on Online Purchasing Decisions (Y).